2006
DOI: 10.1155/jbb/2006/62079
|View full text |Cite
|
Sign up to set email alerts
|

Signaling, Polyubiquitination, Trafficking, and Inclusions: Sequestosome 1/p62′s Role in Neurodegenerative Disease

Abstract: Aggregated misfolded proteins are hallmarks of most neurodegenerative diseases. In a chronic disease state, including pathologic situations of oxidative stress, these proteins are sequestered into inclusions. Accumulation of aggregated proteins can be prevented by chaperones, or by targeting their degradation to the UPS. If the accumulation of these proteins exceeds their degradation, they may impair the function of the proteasome. Alternatively, the function of the proteasome may be preserved by directing agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 86 publications
(132 reference statements)
4
97
0
2
Order By: Relevance
“…α‐Internexin, a neural intermediate filament protein implicated in both AD (Dickson et al ., 2005) and ALS (Page et al ., 2011), was consistently enriched in AD tau‐IP aggregates (Table 2). Sequestosome‐1, which helps to recruit misfolded proteins and their aggregates to either proteasomes or autophagosomes (Wooten et al ., 2006), was highly enriched in tau‐IP aggregates exclusively when derived from AD (Tables 1 and 2). In that context, it is not surprising that tau/Aβ 1–4 PLA signal also colocalizes with punctate immunostain for LC3B/ATG8, a marker of autophagosome membranes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…α‐Internexin, a neural intermediate filament protein implicated in both AD (Dickson et al ., 2005) and ALS (Page et al ., 2011), was consistently enriched in AD tau‐IP aggregates (Table 2). Sequestosome‐1, which helps to recruit misfolded proteins and their aggregates to either proteasomes or autophagosomes (Wooten et al ., 2006), was highly enriched in tau‐IP aggregates exclusively when derived from AD (Tables 1 and 2). In that context, it is not surprising that tau/Aβ 1–4 PLA signal also colocalizes with punctate immunostain for LC3B/ATG8, a marker of autophagosome membranes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Misfolded proteins may result from mutation or as a consequence of conditions, such as oxidative stress, that favor protein unfolding. 13,14,15,18,20 Oxidative stress is also a classical inducer of p62 6,19,24 and therefore seems to be the central player in these disease processes. Moreover, keratin mutations prime hepatocytes to oxidative injury and may thus predispose patients to liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, in a certain context inclusion bodies also may be cytotoxic. 4,[12][13][14][15][16][17][18][19][20][21][22][23][24] The aim of our studies was to obtain closer insight into MB and IHB formation by in vitro transfection of their major components, keratins, p62, and ubiquitin, and correlating the ultrastructure of the resulting aggregates with their chemical composition. Keratin 8 was primarily chosen because we and others have shown that keratin 8 is essential for MB formation in vivo.…”
mentioning
confidence: 99%
“…In response to selinexor alone, Western blot analysis revealed prompt processing and accumulation of LC3 II (Fig. 1A) and sequestosome 1 (p62), an LC3-interacting protein and scavenger of ubiquitinated proteins fated for degradation via autophagy that is also consumed by autophagy (19). Caspase-10 levels decreased modestly during the course of treatment, which is associated with the induction of autophagy in myeloma cells (12).…”
Section: Sine and Pi Treatment Both Induce Hallmarks Of Apoptosis Andmentioning
confidence: 96%